Traditional Magic or European Occultism? Commercial Fortune-Telling and Magic in Post-Soviet Russia and their Relationship to Russian Tradition - Wigzell, Faith (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
The article examines the vibrant commercial magic and fortune- telling industry in Russia today. Based on fieldwork in Petersburg conducted in 2006, supplemented by printed and, in particular, web material, it seeks to show that, despite the many similarities with its counterparts in Europe and North America, Russian fortune-telling and magic are clearly shaped by local traditions. In the context of the article, tradition is taken to include not just rural folk magic and divination, but also urban traditions of the late imperial period as well as those resulting from Soviet policies and practices. It emerges that as far as magic services are concerned, the range of services offered are those demanded by the client, largely stemming from folk tradition. By contrast discourse, approach and ritual often owe much to Western esoteric literature, and perhaps also to pre-Revolutionary occultism and the Soviet interest in psychics. In the case of fortune-telling, today’s professionals (gypsies apart) have adopted more complex and sophisticated ways of telling the future (tarot and astrology). Old ways of fortune-telling are so widely known that they must offer something different to clients. Tradition survives in many ways, sometimes transmuted, sometimes partial, but it makes the Russian magic and fortune-telling scene distinctive.